Adverse Outcomes during Postpartum Readmissions after Deliveries Complicated by Hypertensive Disorders of Pregnancy - Emeruwa, Ukachi N.; Gyamfi-Bannerman, Cynthia; Wen, Timothy; Booker, Whitney; Wright, Jason D.; Huang, Yongmei; D'Alton, Mary E.; Friedman, Alexander M. (American Journal of Perinatology, 2021)
Objective This study aimed to characterize risk for postpartum complications based on specific hypertensive diagnosis at delivery.Study Design This retrospective cohort study used the 2010 to 2014 Nationwide Readmissions Database to identify 60-day postpartum readmissions. Delivery hospitalizations were categorized based on hypertensive diagnoses as follows: (1) preeclampsia with severe features, (2) superimposed preeclampsia, (3) chronic hypertension, (4) preeclampsia without severe features, (5) gestational hypertension, or (6) no hypertensive diagnosis. Risks for 60-day readmission was determined based on hypertensive diagnosis at delivery. The following adverse outcomes during readmissions were analyzed: (1) stroke, (2) pulmonary edema and heart failure, (3) eclampsia, and (4) severe maternal morbidity (SMM). We fit multivariable log-linear regression models to assess the magnitude of association between hypertensive diagnoses at delivery and risks for readmission and associated complications with adjusted risk ratios (aRR) as measures of effect.Results From 2010 to 2014, 15.7 million estimated delivery hospitalizations were included in the analysis. Overall risk for 60-day postpartum readmission was the highest among women with superimposed preeclampsia (6.6%), followed by preeclampsia with severe features (5.2%), chronic hypertension (4.0%), preeclampsia without severe features (3.9%), gestational hypertension (2.9%), and women without a hypertensive diagnosis (1.5%). In adjusted analyses for pulmonary edema and heart failure as the outcome, risks were the highest for preeclampsia with severe features (aRR = 7.82, 95% confidence interval [CI]: 6.03, 10.14), superimposed preeclampsia (aRR = 8.21, 95% CI: 5.79, 11.63), and preeclampsia without severe features (aRR = 8.87, 95% CI: 7.06, 11.15). In the adjusted model for stroke, risks were similarly highest for these three hypertensive diagnoses. Evaluating risks for SMM during postpartum readmission, chronic hypertension and superimposed preeclampsia were associated with the highest risks.Conclusion Chronic hypertension was associated with increased risk for a broad range of adverse postpartum outcomes. Risk estimates associated with chronic hypertension with and without superimposed preeclampsia were similar to preeclampsia with severe features for several outcomes.Key Points
Keywords: postpartum readmissions; severe maternal morbidity; preeclampsia; hypertension; hypertensive disorders of pregnancy